(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2019)
This project explored the integration of Responsible Fatherhood within Foster Care Service within Philadelphia Pennsylvania. It was hypothesized that the key to reducing the number of children who are at risk of entering, re-entering and remaining in various systems of care are the social service programs and systems created to meet the needs of children. One element to improve the outcomes for children is to establish that engaging fathers of foster children can be important not only for the potential benefit of a child-father relationship but also for making placement decisions and gaining access to resources for the child. A diverse group of n=22 service providers voluntarily became involved in a multi-year participatory action research to explore the value of building capacity to integrate Responsible Fatherhood practices, programs, and/or initiatives within foster care service delivery and other children and youth servicing systems. The results from the study highlight a substantial distinction between baseline and post-evaluation of the agency’s father readiness. The findings suggest that there were significantly higher scores on the father friendly checklist in the areas of leadership, polices & procedures, staff development, parent programming, and fatherhood. The article summarizes key recommendation for social service agencies to develop initiatives that outreach to fathers not only to connect with their children, but to build a broader support network that enhances child safety, permanency and well-being.